Prevalence of Phosphatidylinositol-3-Kinase (PI3K) Pathway Alterations and Co-alteration of Other Molecular Markers in Breast Cancer - Khoury, Katia; Tan, Antoinette R.; Elliott, Andrew; Xiu, Joanne; Gatalica, Zoran; Heeke, Arielle L.; Isaacs, Claudine; Pohlmann, Paula R.; Schwartzberg, Lee S.; Simon, Michael; Korn, W. Michael; Swain, Sandra M.; et al. (Frontiers in Oncology, 2020)
Background: PI3K/AKT signaling pathway is activated in breast cancer and associated with cell survival. We explored the prevalence of PI3K pathway alterations and co-expression with other markers in breast cancer subtypes. Methods: Samples of non-matched primary and metastatic breast cancer submitted to a CLIA-certified genomics laboratory were molecularly profiled to identify pathogenic or presumed pathogenic mutations in the PIK3CA-AKT1-PTEN pathway using next generation sequencing. Cases with loss of PTEN by IHC were also included. The frequency of co-alterations was examined, including DNA damage response pathways and markers of response to immuno-oncology agents. Results: Of 4895 tumors profiled, 3558 (72.7%) had at least one alteration in the PIK3CA-AKT1-PTEN pathway: 1472 (30.1%) harbored a PIK3CA mutation, 174 (3.6%) an AKT1 mutation, 2682 (54.8%) had PTEN alterations (PTEN mutation in 7.0% and/or PTEN loss by IHC in 51.4% of cases), 81 (1.7%) harbored a PIK3R1 mutation, and 4 (0.08%) a PIK3R2 mutation. Most of the cohort consisted of metastatic sites (n=2974, 60.8%), with PIK3CA mutation frequency increased in metastatic (32.1%) compared to primary sites (26.9%), p<0.001. Other PIK3CA mutations were identified in 388 (7.9%) specimens, classified as “off-label”, as they were not included in the FDA-approved companion test for PIK3CA mutations. Notable co-alterations included increased PD-L1 expression and high tumor mutational burden in PIK3CA-AKT1-PTEN mutated cohorts. Novel concurrent mutations were identified including CDH1 mutations. Conclusions: Findings from this cohort support further exploration of the clinical benefit of PI3K inhibitors for “off-label” PIK3CA mutations and combination strategies with potential clinical benefit for patients with breast cancer.